Tree growth characteristics, soil parameters, and soil organic carbon of highland Juniper and Acacia forests in Southwestern Saudi Arabia - Abbas, Ahmed M.; Ahmed, Mohamed T.; Ibrahim, Khalid A.; Hussain, Ahmed A.; Novak, Stephen J. (Frontiers in Plant Science, 2026)
Variation in SOC affects the global carbon cycle and climate change and it also determines differences in soil fertility and consequently the plant communities growing in different habitats. The overall goal of this study is to determine variation in SOC in the soils associated with two trees that dominate forests in the highlands of southwestern Saudi Arabia. Juniperus procera dominates forests at higher elevation sites and Acacia gerrardi dominate forests at lower elevations in these highlands. Soils of the J. procera study site had significantly higher mean values for SOC content and SOC density, compared to the mean values of the A. gerrardii study site. The mean value of SOC stock at the J. procera study site was higher than that of the A. gerrardii site, but these differences were not significant. Conversely, the value of soil bulk density (SBD) at the A. gerrardii was significantly higher compared to the J. procera study site. Values of SOC content and SBD were inversely related, and this relationship appeared stronger for the J. procera site. The higher SOC values of the J. procera study site appear to be influence by the significantly larger values of DBH, tree radius, and basal area of these trees, compared to the A. gerrardii trees. Values for five of six soil parameters did not differ significantly between the two study sites, but the clay content of the J. procera study site was significantly higher than the A. gerrardii site. SOC variation at the two study sites appears to be influenced by differences in elevation, climate, species identity, soil bulk density, and clay content. However, the relative importance of these factors on SOC variation was not assessed. Additionally, the roles of litterfall and understory vegetation in contributing to the SOC variation of these two forest ecosystems are yet to be determined. Juniperus procera and A. gerrardi, and the communities they occur in, should be the focus of effective management actions because these species and communities play an important role in carbon sequestration and are also important for biodiversity conservation and the maintenance of ecosystem function.